ISOLASI DAN IDENTIFIKASI SENYAWA MINYAK ATSIRI DARI TUMBUHAN SEMBUKAN (Paederia foetida L.) DENGAN METODE KROMATOGRAFI GAS-SPEKTROSKOPI MASSA (GC-MS) - Yuda Pratama, Dewa Gde Agung; Bawa, I Gusti Agung Gede; Gunawan, I Wayan Gede (Jurnal Kimia (Journal of Chemistry); Vol. 10, No. 1 Januari 2016DO - 10.24843/JCHEM.2016.v10.i01.p20, 2016)
Sembukan is a wild plant that is often attached to the house fenced and has a lot of chemicals compound, including essential oil. This study aims to determine the active compounds as antibacterial of sembukan essential oil. One point four mililitres of essential oil was obtained by steam distillation. The essential oils were then tested for antibacterial activity against Escherichia coli and Stapylococcus aureus using the well diffusion method in gel. Identification of the essential oils conducted using Chromatography Gas – Mass Spectroscopy (GC-MS). The results of this study indicated that the essential oils did not have specific antibacterial activity against the bacteria tested. Compounds contained in the essential oils of sembukan were hydrogenated Linalool, Eugenol, Tetradecane, Heksadecane, and Dibutyl phthalate.
Keywords: isolation, identification, essential oil, antibacterial activity, sembukan plant, GC-MS